Character, Liberty and Law - Murphy, J.G. author. aut Link
XIII, 242 p.
Keywords: Jeffrie G. Murphy's third collection of essays further pursues the topics of punishment and retribution that were explored in his two previous collections: Retribution, Justice and Therapy and Retribution Reconsidered. Murphy now explores these topics in the light of reflections on issues that are normally associated with religion: forgiveness, mercy, and repentance. He also explores the general issue of theory and practice and discusses a variety of topics in applied ethics - e.g., freedom of artistic expression, the morality of gambling, and the value of forgiveness in psychological counseling. As always, his perspective may be described as Kantian; and, indeed, this collection contains the first extended piece of Kant scholarship that he has done in years: a long essay on Kant on theory and practice.